2020
DOI: 10.1080/19186444.2020.1771123
|View full text |Cite
|
Sign up to set email alerts
|

Governance and the capital flight trap in Africa

Abstract: The study examines the use of governance tools to fight capital flight by reducing the capital flight trap. Two overarching policy syndromes are addressed in the study. It first assesses whether governance is an effective deterrent to the capital flight trap in Africa, before examining what thresholds of government quality are required to fight the capital flight trap in the continent. The following findings are established. Evidence of a capital flight trap is apparent because past values of capital flight ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 117 publications
1
12
0
Order By: Relevance
“…The effects of socio-political and institutional factors, such as military expenditure, terrorism, political instability, corruption control on capital flight were considered in the studies of Efobi and Asongu (2016), Asongu and Amankwah-Amoah (2018), Asongu et al (2019), Osei-Assibey et al ( 2017), and Asongu and Nnanna (2020), respectively. Generally, they provided evidence of the effects of these non-economic factors on capital flight in Sub-Saharan African countries at one time or the other.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of socio-political and institutional factors, such as military expenditure, terrorism, political instability, corruption control on capital flight were considered in the studies of Efobi and Asongu (2016), Asongu and Amankwah-Amoah (2018), Asongu et al (2019), Osei-Assibey et al ( 2017), and Asongu and Nnanna (2020), respectively. Generally, they provided evidence of the effects of these non-economic factors on capital flight in Sub-Saharan African countries at one time or the other.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We added RCF t−1 , an autoregressive function showing the effects of past values of capital flight on its current value. This is so expressed, following Asongu and Nnanna (2020) who document that the current value of capital flight is a positive function of its past value (hysteresis). More so, the μ is the stochastic term representing those factors outside the model that might influence its outcome.…”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also showed that lagged capital flight, external debt, foreign direct investment and macroeconomic uncertainty induce capital flight in SSA nations. Also, Asongu and Nnanna (2020) looked at how governance measures may be used to combat capital flight by minimizing the capital flight trap. This study found that previous capital flight values positively influence future capital flight values, indicating evidence of a capital flight trap.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These avenues through which capital exits a country's economy, combined with unhealthy domestic macroeconomic and political conditions, result in massive and widespread distortions and loss of confidence by private capital holders. On the macro front, high and persistent inflation, cost of capital differentials, differentials in the rate of return on investment, huge budget deficits, exchange rate devaluation, poor governance, as well as domestic tax cum trade policies may significantly inspire the flight of capital from the domestic economy (Asongu and Nnanna 2020;Asongu and Odhiambo 2019;Gankou et al 2016;Ndikumana 2016;Okoli and Akujuobi 2009;Hermes and Lensink 2000;Cuddington 1987;Lessard and Williamson 1987;Olopoenia 2000).…”
Section: Empirical Literaturementioning
confidence: 99%